1997
DOI: 10.1029/97gl02997
|View full text |Cite
|
Sign up to set email alerts
|

Ground‐based measurements of tropospheric and stratospheric BrO at Arrival Heights, Antarctica

Abstract: Abstract.Ground-based measurements of BrO slant column densities (SCDs) were performed using zenith sky DOAS (Differential Optical Absorption Spectroscopy) during autumn (February'to May) and spring (August to October) of 1995 at Arrival Heights (77.8øS, 166.7øE).In

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
103
1
4

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(119 citation statements)
references
References 16 publications
9
103
1
4
Order By: Relevance
“…Simultaneous observations by ground-based zenith sky DOAS con®rmed the existence of tropospheric BrO (Wittrock et al, 1996). Similar observations by the same method were reported from Sùndre Strùmfjord, Greenland (Miller et al, 1997), and from Arrival Heights, 77X8 S, 166X7 E, Antarctica (Kreher et al, 1997;Kreher, 1996). Ozone reacts quickly with halogen atoms see Eq.…”
Section: Introductionsupporting
confidence: 74%
“…Simultaneous observations by ground-based zenith sky DOAS con®rmed the existence of tropospheric BrO (Wittrock et al, 1996). Similar observations by the same method were reported from Sùndre Strùmfjord, Greenland (Miller et al, 1997), and from Arrival Heights, 77X8 S, 166X7 E, Antarctica (Kreher et al, 1997;Kreher, 1996). Ozone reacts quickly with halogen atoms see Eq.…”
Section: Introductionsupporting
confidence: 74%
“…Barrie et al, 1988), and has now been observed in the Antarctic (Kreher et al, 1997), where the sparse location Correspondence to: H. K. Roscoe (h.roscoe@bas.ac.uk) of measurement sites means that the ozone-poor air is often lifted above the boundary layer by the time it arrives at the site (Wessel et al, 1998;Roscoe et al, 2001). At first there was some speculation that the Arctic ozone loss might be anthropogenic in origin, but it is now known to be a natural process catalysed by bromine compounds.…”
Section: Introductionmentioning
confidence: 75%
“…In situ measurements of BrO in the Antarctic are more limited and have been generally of a short-term nature however are also significant in their findings. Kreher et al (1997) used a zenith sky DOAS instrument to identify sudden large BrO column enhancement during spring 1995 and during four successive austral springs (1999)(2000)(2001)(2002) at Neumeyer. Friess et al (2004Friess et al ( , 2005) used a similar instrument to find that BrO was present in almost all air masses which had previously been in contact with sea-ice surfaces.…”
Section: Introductionmentioning
confidence: 99%